2012
DOI: 10.5171/2012.795679
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Study of Key Barriers in Construction Project Coordination

Abstract: The complexity of the nature of construction makes it one of the most adverse businesses that has ever existed. Construction projects have often suffered from high fragmentation, large waste, poor productivity, cost and time overruns, and conflicts and disputes for a long time. Thus, many new and innovative management and procurement systems in construction are introduced such as partnering, joint venture, alliances, supply chain management, enterprise resource planning (ERP), just in time (JIT), and total qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…Finally, legislations as waste minimization incentive have a relative important index value of 3.32. Thefindings from this study differ from[16] that identified legislation and financial rewards as the two key drivers for waste minimization incentives.…”
contrasting
confidence: 55%
“…Finally, legislations as waste minimization incentive have a relative important index value of 3.32. Thefindings from this study differ from[16] that identified legislation and financial rewards as the two key drivers for waste minimization incentives.…”
contrasting
confidence: 55%
“…On the other hand, facilities shortage as communication channels and tools was less than 1 %, which is not significant. The above numbers mean that, more training and awareness need to be implemented to overcome the ability and willingness problem, respectively [17]. The adversary relationship between construction parties diploma can be reduced through the well-prepared contract and the early responsibilities distribution [1,13].…”
Section: Resultsmentioning
confidence: 99%
“…Several relevant studies were reviewed to derive the coordination characteristics on construction projects. Hai et al, [17] states coordination process is an actual synchronization of the prearranged work efforts within citrine characteristics. The most important characteristic is the knowledge level about coordination process in construction projects management, which represent the general awareness of the coordination process [14,18].…”
Section: Principle Of Reciprocal Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…e main concern and principle of coordination focus on the organization, interdependent links, relationships, information exchange, and common objectives between involved parties [17].…”
Section: Coordination In Constructionmentioning
confidence: 99%